2018
DOI: 10.1002/asia.201800264
|View full text |Cite
|
Sign up to set email alerts
|

Design of Conjugated Molecules Presenting Short‐Wavelength Luminescence by Utilizing Heavier Atoms of the Same Element Group

Abstract: The introduction of heavy atoms into conjugated molecules often induces a redshift in the emission spectra. Conversely, we report here a blueshifting effect in the absorption and emission bands of a conjugated organic dye by employing a heavier atom from the same element group. Boron complexes having oxygen- and sulfur-bridged structures in the ligand moiety were synthesized, and their optical properties were compared. Significant optical bands in the absorption and luminescence spectra of the sulfur-bridged c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Enaminone compounds have been widely used for the formation of highly emissive metal or boron complexes . However, fluorescence properties of pure enaminone compounds have rarely been mentioned, especially in the solid states .…”
Section: Methodsmentioning
confidence: 99%
“…Enaminone compounds have been widely used for the formation of highly emissive metal or boron complexes . However, fluorescence properties of pure enaminone compounds have rarely been mentioned, especially in the solid states .…”
Section: Methodsmentioning
confidence: 99%
“…Based on this idea, the pyridinoiminate complex BPI was obtained ( Figure 13). 73,74 A large difference between optimized structures in the ground and excited states, which can be obtained by the calculations with density functional theory (DFT) and time-dependent DFT methods, respectively, was proposed. 73 Therefore, it was expected that boron pyridinoiminate can work as an AIE behavior.…”
Section: Figures 10 and 11mentioning
confidence: 99%
“…However, recent studies have demonstrated that DBF shows better charge-transporting properties and solubility than DBT. 24,25 The small oxygen atom size endows DBF with smaller torsional angles and higher planarity, which is beneficial for orderly stacking and charge transport in the solid state. 24,26 Even more striking is that furan derivatives can avoid the heavy atom effect that occurs in thiophene-based luminogens.…”
Section: Design and Synthesis Of The Compoundsmentioning
confidence: 99%
“…24,26 Even more striking is that furan derivatives can avoid the heavy atom effect that occurs in thiophene-based luminogens. 25 Thus, they tend to exhibit stronger and short-wavelength luminescence and are promising candidates for fabricating advanced full-color display optoelectronic devices. o-Carborane was selected to tune the excited state of organic chromophores.…”
Section: Design and Synthesis Of The Compoundsmentioning
confidence: 99%